Pola Pembinaan dan Pengembangan Lembaga Pendidikan Islam melalui Kepemimpinan Kepala Madrasah Yang Ideal - Mar'atul Azizah (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2018)
The leader quality in an organization determines whether or the organization reach the goal expected. There are two basic capacities as main points should be owned for a leader and as ideal requirement for the leader in the institution, they are managerial skill dan technical skill. Whether the leader will be succeed or not in conducting their leadership, however, determined not only on their technical skill, but more on their managerial skill, in this case their skill in making people to work. Madrasa is one of educational institution which has an importance existence in improving the nation’s intelligence, makes effort to improve the quality education out put which has been complained community by fostering and developing the Islamic educational institution. The form of fostering and developing is private empowerment. The private madrasa is the growth of educational institution root in the environment of Ministry of religion, and it is the largest part of the madrasa in Indonesia.